Silent Threat: Uncovering the Increase in Non-Compliance of Pediatric Prediabetes Cases in the Digital Age - Hutapea, Dwight Mahaputera Marulitua (MSJ : Majority Science Journal, 2025)
The prevalence of prediabetes in children has shown a significant increase globally, including in Indonesia, along with lifestyle changes due to digitalization and urbanization. Children are now at risk of earlier onset of metabolic disorders, exacerbated by unhealthy diets, lack of physical activity, and high exposure to digital media and processed food advertisements. This condition often goes undetected due to the asymptomatic nature of prediabetes, while the transition to type 2 diabetes can occur without early intervention. This study uses a qualitative approach through literature studies to examine factors that influence non-compliance with prediabetes management in children in the digital era. Data sources were obtained from scientific journals and reports from trusted health institutions in the period 2015–2025, and analyzed using thematic techniques. The results of the study indicate that low health literacy, the dominance of a digital culture that supports a sedentary lifestyle, and minimal early detection in primary health services are the main obstacles. A cross-sectoral strategy involving families, schools, and the government is needed to increase awareness, strengthen nutrition education, and reform the child health care system to be able to face the challenges of prediabetes as a hidden epidemic in the future.